An Analysis of Joint Venture Agreements and its Financing Mechanisms - Conde Granados, Jorge Luis (2015)
The untitled Article Analysis of the Contract of Joint Venture and his Financing’s Mechanisms, it is very interesting contribution since the civil structure of the contract attempts to lay eggs in knowledge and whose objective or end is of entrepreneurial nature. Seeing as of the present moment more and more the foreign investors look for the way to deposit of her his local associate’s hands for determined projects to the foreign markets or I have operations, which once the negotiation was concretized, the wording of Joint Venture’s contract will be fundamental to avoid any interrogation in the future, there where you establish what’s vital to know the civil structure and the elements of the contract and which finds itself technically developed in the present Article. Finally, the author attempts to understand the financing like important element to operate the aforementioned contract, for which shows us I hire some of the more mechanisms utilized in a moment to go into validity of the